An Evidence-Based Model of Multidisciplinary Care for Patients and Families Affected by Classical Congenital Adrenal Hyperplasia due to 21-Hydroxylase Deficiency. (28th February 2010) - Schaeffer, Traci L.; Tryggestad, Jeanie B.; Mallappa, Ashwini; Hanna, Adam E.; Krishnan, Sowmya; Chernausek, Steven D.; Chalmers, Laura J.; Reiner, William G.; Kropp, Brad P.; Wisniewski, Amy B.
Abstract : In 2002 a consensus statement pertaining to the management of classical congenital adrenal hyperplasia due to 21-hydroxylase deficiency was jointly produced by the Lawson Wilkins Pediatric Endocrine Society and the European Society of Pediatric Endocrinology. One of the recommendations of this consensus was that centers should maintain multidisciplinary teams for providing care and support to these patients and their families. However, the specifics for how this should be accomplished were not addressed in the original consensus statement. Here we interpret and translate the 2002 consensus statement recommendations into medical, surgical and mental health protocols. Additionally, we provide preliminary evidence that such protocols result in improved care and support for patients and families.